2015
DOI: 10.5732/cjc.014.10146
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-type protein tyrosine phosphatases in cancer

Abstract: Protein tyrosine phosphatases (PTPs) play an important role in regulating cell signaling events in coordination with tyrosine kinases to control cell proliferation, apoptosis, survival, migration, and invasion. Receptor-type protein tyrosine phosphatases (PTPRs) are a subgroup of PTPs that share a transmembrane domain with resulting similarities in function and target specificity. In this review, we summarize genetic and epigenetic alterations including mutation, deletion, amplification, and promoter methylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
72
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 84 publications
0
72
0
Order By: Relevance
“…In this study, we aimed to focus instead on investigating the 3D microenvironment-related factors and mechanisms that may have contributed to the enhanced migration of glioma cells when encapsulated in 3D CS-GAG matrices as observed in the in vitro microfluidics based migration assays. We specifically focused on evaluating the gene and protein expression patterns of the chemokine CXCL12 and its high-affinity receptor CXCR4; as well as the cell surface receptor LAR since these factors have been implicated in CS-GAG mediated glioma cell haptotaxis, and CSPG binding respectively 18, 4648 . Previous evidence also suggests that the extracellular tumor microenvironment could facilitate cytoskeletal rearrangement leading to glioma cell invasion 4952 .…”
Section: 0 Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we aimed to focus instead on investigating the 3D microenvironment-related factors and mechanisms that may have contributed to the enhanced migration of glioma cells when encapsulated in 3D CS-GAG matrices as observed in the in vitro microfluidics based migration assays. We specifically focused on evaluating the gene and protein expression patterns of the chemokine CXCL12 and its high-affinity receptor CXCR4; as well as the cell surface receptor LAR since these factors have been implicated in CS-GAG mediated glioma cell haptotaxis, and CSPG binding respectively 18, 4648 . Previous evidence also suggests that the extracellular tumor microenvironment could facilitate cytoskeletal rearrangement leading to glioma cell invasion 4952 .…”
Section: 0 Discussionmentioning
confidence: 99%
“…LAR protein tyrosine phosphatases have also been documented as being overabundant in a multitude of different cancers as a marker of invasiveness 46 . We found that the presence of sulfated CS-GAGs in the extracellular microenvironment stimulates the significant overexpression of the CSPG binding LAR transcript in encapsulated glioma cells, which may have contributed to the observed increase in F-actin polymerization and colocalization of cytoskeletal adhesion proteins in encapsulated glioma cells.…”
Section: 0 Discussionmentioning
confidence: 99%
“…The tumor suppressive functionality of PTPs, including the PTPRD gene, is further supported by homozygous deletions and loss-of-function mutations observed in various human neoplasms. 1,3,11,12 Nevertheless, considering the frequency of transcriptional silencing of PTPRD, additional mechanism must be co-responsible for its inactivation. In line with this hypothesis, in the eight LSCC cell lines sequenced in this study, which showed no expression of the PTPRD gene, beside the observed SNPs, none harbored a loss-of-function mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Therein, the inactivating PTPs function in a delicate balance with the activating protein tyrosine kinases. 1 Various alterations resulting in loss of function of the PTP genes observed in neoplasms emphasize their suppressive role in cancer formation. 2 Recently, we reported homozygous deletions that target the PTPRD gene in laryngeal squamous cell carcinoma (LSCC) cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…PTPs have also been indicated as important regulators in tumorigenesis and angiogenesis (1518). Receptor-like protein tyrosine phosphatase beta (PTPRB, also known as vascular endothelial VE-PTP), for example, plays a crucial role in the angiogenesis of breast cancer by regulating several signalling pathways such as the Tie-2 pathway (19).…”
Section: Introductionmentioning
confidence: 99%